2022
DOI: 10.1039/d1mo00267h
|View full text |Cite
|
Sign up to set email alerts
|

Delineating toxicity mechanisms associated with MRI contrast enhancement through a multidimensional toxicogenomic profiling of gadolinium

Abstract: Although gadolinium is widely used for magnetic resonance imaging in clinical settings, many concerns regarding its toxicity and bioaccumulation after gadolinium-based contrast agent (GBCA) administration have been raised and published...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 94 publications
2
6
1
Order By: Relevance
“…These results agreed with the previous literature, which reported that heavy metals disrupt the biological functions of proteins and enzymes as well as the processes that these biomolecules regulate. 56 It is worth noting that these results are substantially different from what was observed and previously reported with later lanthanides for which a similar analysis was performed: neither europium 43 nor gadolinium 46 displayed such significant metal-induced toxicity even under the greater IC 10 exposure conditions at 15 generations.…”
Section: Resultscontrasting
confidence: 97%
See 3 more Smart Citations
“…These results agreed with the previous literature, which reported that heavy metals disrupt the biological functions of proteins and enzymes as well as the processes that these biomolecules regulate. 56 It is worth noting that these results are substantially different from what was observed and previously reported with later lanthanides for which a similar analysis was performed: neither europium 43 nor gadolinium 46 displayed such significant metal-induced toxicity even under the greater IC 10 exposure conditions at 15 generations.…”
Section: Resultscontrasting
confidence: 97%
“…These different times of exposure are commonly used in toxicogenomics because they allow determination of time-dependent responses and delayed onset effects. 40 , 41 Sensitive and resistant mutants to the metal treatments were identified by DSSA, 46 with their growth variations reported in the log 2 scale in Dataset S1 and the total number of mutants affected under each treatment plotted ( Figure 1 a). The growth of only a few mutants (between 1 and 40) was disturbed at low lanthanide concentrations (IC 5 ) or low exposure time (10 generations).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Free radioisotopes and metals, particularly f-block elements, have high binding affinities for biological receptors (30,31), resulting in their endogenous chelation and subsequent deposition in tissues (32,33). Internal contamination with radiometals (and their decay products) cause metal-and radiotoxicity, as multiple biological processes get disrupted (34)(35)(36)(37)(38)(39). Therefore, minimizing daughter release is a fundamental step to extend the use of targeted alpha therapy beyond metastatic non-responding patients (28).…”
Section: Introductionmentioning
confidence: 99%